Corporate Environmental Responsibility Model Based on Indonesian Ecocentric Principles - Taufik, Taufik; Yulianingrum, Aullia Vivi; Elviandri, Elviandri; Hasmiati, Ayu (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Abstract Corporate environmental responsibility (CER) is an increasingly significant concept in the modern era, especially in Indonesia, which has abundant natural resources but is vulnerable to exploitation. CER is not only understood as a legal and ethical obligation, but also as a new paradigm that places ecological awareness at the core of business activities. This study aims to analyse a model of corporate environmental responsibility based on ecocentric principles that emphasise balance and harmony between humans and nature. The ecocentric approach requires corporations to go beyond a profit-only orientation by considering the social and environmental impacts of their operational activities. Through normative analysis and case studies in the mining and plantation sectors in Indonesia, this study explores how ecocentric values can be integrated into sustainable business strategies. The results show that the implementation of ecocentric CER has the potential to enhance corporate reputation, strengthen social relations with local communities, and support sustainable environmental conservation. Furthermore, the effectiveness of CER implementation is greatly influenced by government policies and regulations, such as incentives for the application of environmentally friendly technologies and the enforcement of sanctions for environmental violations. Collaboration between the government, corporations, and the community is key to building a business ecosystem that is ecologically just and oriented towards sustainability. In conclusion, CER is not only a moral responsibility, but also a business strategy that is adaptive to market demands and global awareness of environmental issues. Integrating ecocentric values into corporate governance is a strategic step in realising sustainable development that is in line with the principles of ecological justice and shared prosperity. [Tanggung jawab lingkungan korporasi (CER) merupakan konsep yang semakin penting di era modern, terutama di Indonesia yang kaya akan sumber daya alam namun rentan terhadap eksploitasi. CER tidak hanya dipahami sebagai kewajiban hukum dan etika, tetapi juga sebagai paradigma baru yang menempatkan kesadaran ekologis sebagai inti dari aktivitas bisnis. Studi ini bertujuan untuk menganalisis model tanggung jawab lingkungan korporasi berdasarkan prinsip-prinsip ekosentris yang menekankan keseimbangan dan harmoni antara manusia dan alam. Pendekatan ekosentris mengharuskan perusahaan untuk melampaui orientasi profit semata dengan mempertimbangkan dampak sosial dan lingkungan dari aktivitas operasional mereka. Melalui analisis normatif dan studi kasus di sektor pertambangan dan perkebunan di Indonesia, penelitian ini mengeksplorasi bagaimana nilai-nilai ekosentris dapat diintegrasikan ke dalam strategi bisnis berkelanjutan. Hasil penelitian menunjukkan bahwa implementasi CER ekosentris berpotensi meningkatkan reputasi korporasi, memperkuat hubungan sosial dengan komunitas lokal, dan mendukung konservasi lingkungan yang berkelanjutan. Selain itu, efektivitas implementasi CER sangat dipengaruhi oleh kebijakan dan regulasi pemerintah, seperti insentif untuk penerapan teknologi ramah lingkungan dan penegakan sanksi terhadap pelanggaran lingkungan. Kerja sama antara pemerintah, korporasi, dan masyarakat merupakan kunci dalam membangun ekosistem bisnis yang adil secara ekologis dan berorientasi pada keberlanjutan. Kesimpulannya, CER bukan hanya tanggung jawab moral, tetapi juga strategi bisnis yang adaptif terhadap permintaan pasar dan kesadaran global terhadap isu lingkungan. Mengintegrasikan nilai-nilai ekosentris ke dalam tata kelola korporasi merupakan langkah strategis dalam mewujudkan pembangunan berkelanjutan yang sejalan dengan prinsip keadilan ekologis dan kemakmuran bersama.]